The training process: Planning for strength-power training in track and field. Part 2: Practical and applied aspects - DeWeese, B. H.; Hornsby, G.; Stone, M.; Stone, M. H. (Journal of Sport and Health Science, 2015)
Planning training programs for strength-power track and field athletes require an understanding of both training principles and training theory. The training principles are overload, variation, and specificity. Each of these principles must be incorporated into an appropriate system of training. Conceptually, periodization embraces training principles and offers advantages in planning, allowing for logical integration and manipulation of training variables such as exercise selection, intensification, and volume factors. The adaptation and progress of the athlete is to a large extent directly related to the ability of the coach/athlete to create and carry an efficient and efficacious training process. This ability includes: an understanding of how exercises affect physiological and performance adaptation (i.e., maximum force, rate of force development, power, etc.), how to optimize transfer of training effect ensuring that training exercises have maximum potential for carryover to performance, and how to implement programs with variations at appropriate levels (macro, meso, and micro) such that fatigue management is enhanced and performance progress is optimized.